Concentrations of Se, Ba, Zn and Mn in Brazil nuts (Brazilian Journal of Radiation Sciences (BJRS), 2019)
The concentrations of Se, Ba, Zn and Mn were determined in samples of Brazil nuts collected in two ways: a) in a production farm predominantly for export and, b) in various points of sale from different regions of Brazil. Instrumental neutron activation analysis was the analytical technique used in this study. Results indicate that the concentrations of Se and Ba varied greatly among the Brazil nut samples analyzed. This large variability may be related to the soil characteristics from which the nuts were produced. An inverse correlation was observed between the concentrations of Se and Ba. On the other hand, the concentrations of Zn and Mn did not show significant differences among these samples.